Buddhism Co. Ltd? Epistemology of religiosity, and the re-invention of a Buddhist monastery in Hong Kong - QIAN, Junxi (Institutional Knowledge at Singapore Management University, 2018)
This article re-theorises the relationships between secularity and religiosity in modernity. While geographers have recognised that the secular and the religious are mutually constituted, this article pushes this theorisation further, arguing that the religious and the secular are in fact hybrid constructs that embrace simultaneously the sacred and profane, the transcendent and the immanent. Albeit the significant advancement in disrupting enclosed epistemologies of secular modernity, relatively less work has sought to theorise the possibility of religion as a hybrid operating at the secular–religious interface. Focusing on the ways in which a non-Western religion, Buddhism, performs entangled relationships between religiosity and secularity, this article argues that religious organisations and actors may refashion and re-invent themselves by appropriating rationalities, values and logics normatively defined as ‘secular’. It presents a study of Po-Lin Monastery, a Buddhist monastery in Hong Kong that has adopted highly entrepreneurial, growth-oriented approaches in organisation and production of space.